Enhanced visible-light-response photocatalytic degradation of methylene blue on Fe-loaded BiVO4photocatalyst - Sinaporn Chala (2018)
Pure BiVO4and nominal 0.5-5.0 mol% Fe-loaded BiVO4samples were synthesized by hydrothermal method. All samples were characterized in order to obtain the correlation between structure and photocatalytic properties by X-ray diffraction, Brunauer, Emmett and Teller, UV-vis diffuse reflectance spectrophotometry, photoluminescence spectroscopy, transmission electron microscopy, X-ray photoelectron spectroscopy and inductively coupled plasma-optical emission spectroscopy. The structure of all samples was single-phase monoclinic scheelite. The absorption spectrum of 5.0 mol% Fe-loaded BiVO4shifted to the visible region, suggesting the potential application of this material as a superior visible-light driven photocatalyst in comparison with pure BiVO4. Photocatalytic activities of all photocatalyst samples were examined by studying the degradation of methylene blue under visible light irradiation. The results clearly showed that Fe-loaded BiVO4sample exhibited remarkably higher activity than pure BiVO4. © 2014 Elsevier B.V. All rights reserved.